RANCANG BANGUN APLIKASI PERAMALAN NILAI SAHAM MENGGUNAKAN ALGORITMA KALMAN FILTER - Erwin Ruslim Sia; Seng Hansun (Komputa : Jurnal Ilmiah Komputer dan Informatika, 2014)
Every prediction have different probability, including prediction in stock market. In order to give the best prediction with the highest probability, we try to determine how Kalman Filter, an algorithm that uses recursive function to predict future value, produce high probability in predicting stock price. There are two set of data companies that are used in this application, namely XL Axiata Tbk. with success percentage at 95,83%, and Astra Agro Lestari Tbk. with success percentage at 95,07%. This application is developed using C# programming language and SQL SERVER.